College students’ perceptions of using an online automated essay scoring system - TSAI CHIA-CHING; SHAN CHUAN-KUO (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aimed to examine how students felt about and responded to using the PIGAI system in their English composition courses. Students’ impressions and responses to AES initiatives were also investigated.Method: Twenty-five undergraduates enrolled in an English Writing Course participated in this quantitative and qualitative study. This study utilized a survey created in 2016 by Professor He, Huaqing of China West Normal University for its quantitative approach. After the survey was completed, interviews with a total of 6 participants were conducted to collect data using the qualitative approach.Findings: Positive attitudes were shown toward the PIGAI system, particularly in vocabulary and grammar, among the students. Interestingly, those students who already had a high level of English proficiency complained that the system gave them inaccurate information and lower scores than expected. They also noted the importance of the instructor’s comments to their development as writers. On the other hand, students with a lower command of English saw it as a useful tool that could help them feel more comfortable with the written word before turning in an essay.Implications/Novel Contribution: Our data shows that instructors and academics need to design writing courses with a healthy respect for the AES system and the instructor’s comments in mind. The findings could provide useful insight into fundamental facets of integrating the AES and instructor feedback into writing lessons.